Effect of vegetation cover on dung beetles (Coleoptera: Scarabaeinae) and their ecological functions in an Andean forest of Colombia - Arias-Álvarez, Gustavo Adolfo; Vanegas-Alarcón, David Andrés; García-Hernández, Andrea Lorena; Santos-Heredia, Carolina; Andresen, Ellen (Revista de Biología Tropical, 2022)
Introduction: Dung beetles perform important functions in terrestrial ecosystems, but anthropic pressures negatively affect them. These effects are well documented for Neotropical lowland forests, but have been little studied in Andean forests. Objectives: To evaluate how the attributes of dung beetle communities and three of their ecological functions differ in three land uses at the "Hacienda El Ocaso". Additionally, the relationships between attributes and functions, and among the tree different functions, were evaluated. Methodology: Using pitfall traps, dung beetles were sampled in three vegetation covers representing different land uses: secondary forest, mixed forest and livestock pastures (three independent sites per cover). The community attributes that were evaluated were abundance, number of species, biomass, and community weighted mean of body length; the functions that were measured were faeces removal, soil excavation, and secondary seed dispersal. Results: It was found that both community attributes and ecological functions are being negatively affected by the change in land use, mainly by livestock use. Most of the community attributes were positively correlated with functions; soil excavation and seed dispersal were strongly correlated with the removal of faeces. Conclusion: This study contributes to our understanding of the dung beetle fauna and its functional importance in the forests of the Andean region and how they are affected by land use change.